Preliminary study of balance and substance flows of phosphorus and cadmium in the agricultural soil of Songkhla Lake catchment = การศึกษาเบื้องต้นของสมดุลสารและการเคลื่อนที่ของฟอสฟอรัสและแคดเมียมในพื้นที่เกษตรกรรมลุ่มน้ำทะเลสาบสงขลา - Wassanar Sereewatthanachai (Prince of Songkla University, 2003)
Master of Science (Environmental Management)